An Analysis Of Politeness Principle Of Main Character In “MOANA” Movie - Melga J Capah; Fenty Debora Napitupulu; Carolina Pakpahan; Samuel J Sinaga (Innovative: Journal Of Social Science Research, 2023)
This study deals with the analysis of types of Politeness Principle are used by main character in Moana Movie and what the dominant types of politeness principle are used by main character in Moana movie. The objective of this study was to analyze types of politeness principle maxim wich are used in Moana Movie and To find out the dominant types of politeness principle maxim in Moana Movie. This research used a qualitative method by selecting and collecting data from Moana movie. After selecting and collecting the data, the researchers identify and analyze the utterances in conversations among characters and used the concept of Geoffrey Leech related to pragmatics study. The result shows that: (1) Politeness Principle categorized as tact maxim 6 data, generosity maxim 3 data, approbation maxim 8 data, modesty maxim 5 data, agreement maxim 6 data, and symphaty maxim 5 data. (2) the precentage of types of Politeness Principle are tact maxim 18 % , generosity maxim 9 %, approbation maxim 24 %, modesty maxim 15 %, agreement maxim 18 %, and symphaty maxim 15 %.